Reducing agents facilitate membrane patch seal integrity and longevity - Damayantee Das; Anson Wong; Timothy N. Friedman; Bradley J Kerr; Harley T. Kurata; Shawn M. Lamothe (Channels)
The patch clamp method is a widely applied electrophysiological technique used to understand ion channel activity and cellular excitation. The formation of a high resistance giga-ohm seal is required to obtain high-quality recordings but can be challenging due to variables including operator experience and cell preparation. Therefore, the identification of methods to promote the formation and longevity of giga-ohm seals may be beneficial. In this report, we describe our observation that the application of reducing agents (DTT and TCEP) to the external bath solution during whole-cell patch clamp recordings of heterologous cells (HEK and LM) and cultured primary cells (DRG neurons) enhanced the success of giga-ohm seal formation. Reducing agents also maintained the integrity of the seal for longer periods of time at strong hyperpolarizing voltages, whereas an oxidizing agent (H2O2) appeared to have the opposite effect. In summary, we report a useful tool to improve the quality of patch clamp recordings that may be helpful in certain experimental contexts.